Antropomorfisme Ilahi dalam Kejadian 11:5: Kajian Eksegetis Historis–Gramatikal terhadap Ungkapan “TUHAN Turun Melihat” dalam Perspektif Teologi Perjanjian Lama - Yalsin Triadi; Fernando Randa Ma’dika (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study examines the anthropomorphic expression “the LORD came down to see” in Genesis 11:5 through an integrated historical–grammatical exegetical approach. The main objective is to analyze the lexical meaning, grammatical structure, historical context, and theological implications of the phrase within the framework of Old Testament theology. The research employs a qualitative library method, focusing on the Hebrew text supported by lexicons, commentaries, and Ancient Near Eastern studies. The findings indicate that the verb יָרַד (yārad) does not merely denote a spatial descent but signifies divine intervention, while רָאָה (rāʾāh) conveys evaluative and judicial observation. Grammatically, the use of the wayyiqtol form followed by an infinitive construct emphasizes intentional and purposeful divine action. Historically, the expression functions polemically against Mesopotamian religious concepts, particularly the idea of ziggurats as places where deities descend. Theologically, this anthropomorphic language serves as a medium to articulate the dynamic relationship between divine transcendence and immanence. Therefore, the phrase should not be understood literally but as a theological construct that communicates God’s active involvement and sovereign authority in human history.